THE CHANGE OF SALIVARY pH AFTER RINSING WITH FUJI APPLE (Malus sylvestris) EXTRACT 100% ON CHILDREN AGED 8-10 YEARS. (Review onstudents in SDN Pengambangan 3 Banjarmasin) - Dian Dwiyanti; Didit Aspriyanto; Isyana Erlita (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: The age of 8-10 is the age group with highest number of dmf-t in children. The normal salivary pH can prevent the formation of caries. Fuji apple has contents that are antibacterial such as flavonoid, catechin and tannin that reduce the production of salivary acid by Streptococcus mutanbactery. Purpose: To analyze the difference change of pH saliva before and after rinsing with Fuji apple (Malus sylvestris) extract100% and Chlorhexidine 0,2% in oral cavity of children aged 8-10 years old. Method: This study used quasi experimental method with pre-post test control group design. The samples were determined by purposive random sampling on children aged 8-10 years old in SDN Pengambangan 3 Banjarmasin with the total of 63 people. Samples were divided to 3 treatment groups which are rinsing with Fuji apple (Malus sylvestris) extract 100%, Chlorhexidine 0,2% and aquades. Result: The result of One-way Anova test showed that there was difference on the three treatment groups (p=0,0001). The result of Posthoc Bonferroni test showed that there was significant difference between Fuji apple (Malus sylvestris) extract 100%, Chlorhexidine 0,2% (p=0,016). There was significant difference between Fuji apple (Malus sylvestris) extract 100% and Aquades (p=0,0001) and between Chlorhexidine 0,2% andaquades (p=0,0001). The increase of salivary pH was found in three groups treatment. Conclusion: There is significant difference between groups that rinse with Fuji apple (Malus sylvestris) extract and Chlorhexidine 0,2% in children aged 8-10 years old.